KOMUNIKASI INTERPERSONAL PSIKOLOG TERHADAP PEMULIHAN PASIEN RUMAH SAKIT JIWA PROVINSI SUMATERA UTARA - Satria Lanri Simanjuntak; Nurhasanah Nasution (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2017)
In the process of recovery patients mental hospital, communication is needed by a psychologist. No exception for patients madhouse north sumatra who need motivation, advice and support for recovery patients one using interpersonal communication to the patient that interwoven rapport good between psychologist and patients. The purpose of this research is to find communication interpersonal psychologist to replenish patients madhouse north sumatra.Methods used in this research is descriptive of qualitative methods with the collection of data through interviews and research literature available. The result of this show that interpersonal communication psychologist against recovery patient mental hospital north sumatra province is needed because of the communication that is psychologist can know the problems suffered by patients,  and from psychologist communication also help the healing process. Psychologist provide support, advice, as well as motivation to patient can be recovered. Keywords: communication interpersonal, mental hospital, psychologist